2022
DOI: 10.1123/japa.2021-0256
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Intervention of Physical Activity Education and Counseling in Community Rehabilitation: A Feasibility Randomized Controlled Trial

Abstract: This study aimed to assess the feasibility of delivering a brief physical activity (PA) intervention to community rehabilitation clients. Participants were randomized to receive one session of stage-of-change-based PA education and counseling in addition to written educational material, or education material alone. Outcomes were measured at baseline and 3 months; the primary outcome was feasibility, measured by the percentage of those who were eligible, consented, randomized, and followed-up. A total of 123 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Thirteen studies examined a single session brief intervention, 24–27,29,30,35,36,42–44,46,47 with four using technology for delivery 26,27,30,47 (i‐pad, DVD, computer program). Nine studies included a single brief counselling session with follow up by either mail or phone call 23,28,31–34,37,38,41 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies examined a single session brief intervention, 24–27,29,30,35,36,42–44,46,47 with four using technology for delivery 26,27,30,47 (i‐pad, DVD, computer program). Nine studies included a single brief counselling session with follow up by either mail or phone call 23,28,31–34,37,38,41 .…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes reported were self-reported PA minutes/day (n = 15 studies [24][25][26]28,[31][32][33]35,37,38,[41][42][43][44]46,47 ), self-reported MET (metabolic equivalent)/day of PA (n = 5 studies 23,27,28,30,34 ), pedometer steps/ day (n = 4 studies 28,39,40,45 ) and PA using activity monitors (n = 3 studies 28,35,36 ). Secondary review outcomes reported included: QoL (n = 6 studies 23,[34][35][36]39,40,45 ); self-efficacy for exercise (n = 7 studies 30,31,33,36,[42][43][44] ); and, stage of change in relation to exercise (n = 2 studies 30,36 ). Three studies reported adherence to prescribed walking interventions from patient-reported activity logs 23,28,46 with mean adherence ranging from 62%…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations